A Novel Cold-Adapted Leucine Dehydrogenase from Antarctic Sea-Ice Bacterium Pseudoalteromonas sp. ANT178 - Yatong Wang; Yanhua Hou; Yifan Wang; Lu Zheng; Xianlei Xu; Kang Pan; Rongqi Li; Quanfu Wang (Marine Drugs, 2018)
l-tert-leucine and its derivatives are useful as pharmaceutical active ingredients, in which leucine dehydrogenase (LeuDH) is the key enzyme in their enzymatic conversions. In the present study, a novel cold-adapted LeuDH, psleudh, was cloned from psychrotrophic bacteria Pseudoalteromonas sp. ANT178, which was isolated from Antarctic sea-ice. Bioinformatics analysis of the gene psleudh showed that the gene was 1209 bp in length and coded for a 42.6 kDa protein containing 402 amino acids. PsLeuDH had conserved Phe binding site and NAD+ binding site, and belonged to a member of the Glu/Leu/Phe/Val dehydrogenase family. Homology modeling analysis results suggested that PsLeuDH exhibited more glycine residues, reduced proline residues, and arginine residues, which might be responsible for its catalytic efficiency at low temperature. The recombinant PsLeuDH (rPsLeuDH) was purified a major band with the high specific activity of 275.13 U/mg using a Ni-NTA affinity chromatography. The optimum temperature and pH for rPsLeuDH activity were 30 °C and pH 9.0, respectively. Importantly, rPsLeuDH retained at least 40% of its maximum activity even at 0 °C. Moreover, the activity of rPsLeuDH was the highest in the presence of 2.0 M NaCl. Substrate specificity and kinetic studies of rPsLeuDH demonstrated that l-leucine was the most suitable substrate, and the catalytic activity at low temperatures was ensured by maintaining a high kcat value. The results of the current study would provide insight into Antarctic sea-ice bacterium LeuDH, and the unique properties of rPsLeuDH make it a promising candidate as a biocatalyst in medical and pharmaceutical industries.